Comprehensive functional analysis of the PYL-PP2C-SnRK2s family in Bletilla striata reveals that BsPP2C22 and BsPP2C38 interact with BsPYLs and BsSnRK2s in response to multiple abiotic stresses - Liu, Shuai; Lu, Chan; Jiang, Guanghui; Zhou, Ru; Chang, Yuanqing; Wang, Shiqiang; Wang, Donghao; Niu, Junfeng; Wang, Zhezhi (Frontiers in Plant Science, 2022)
As the core regulation network for the abscisic acid (ABA) signaling pathway, the PYL-PP2C-SnRK2s family commonly exists in many species. For this study, a total of 9 BsPYLs, 66 BsPP2Cs, and 7 BsSnRK2s genes were identified based on the genomic databases of Bletilla striata, which were classified into 3, 10, and 3 subgroups, respec-tively. Basic bioinformatics analysis completed, including the physicochemical proper-ties of proteins, gene structures, protein motifs and conserved domains. Multiple cis-acting elements related to stress responses and plant growth were found in promoter regions. Further, 73 genes were localized on 16 pseudochromosomes and 29 pairs of paralogous genes were found via intraspecific collinearity analysis. Furthermore, tis-sue-specific expression was found in different tissues and germination stages. There were 2 BsPYLs, 10 BsPP2Cs, and 4 BsSnRK2 genes that exhibited a difference in re-sponse to multiple abiotic stresses. Moreover, subcellular localization analyses revealed six important proteins BsPP2C22, BsPP2C38, BsPP2C64, BsPYL2, BsPYL8, and BsSnRK2.4 which were localized in the nucleus and plasma membrane. Finally, yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays sug-gested that BsPP2C22 and BsPP2C38 could interact with multiple BsPYLs and BsS-nRK2s proteins. This study systematically reported on the identification and characteri-zation of the PYL-PP2C-SnRK2s family in B. striata, which provided a conceptual ba-sis for deep insights into the functionality of ABA core signal pathways in Orchidaceae.